Pyrophosphate-stabilised amorphous calcium carbonate for bone substitution: toward a doping-dependent cluster-based model. Issue 45 (4th November 2022) - Merle, Marion; Soulié, Jérémy; Sassoye, Capucine; Roblin, Pierre; Rey, Christian; Bonhomme, Christian; Combes, Christèle
Abstract : Multiscale and multitool advanced characterisation of pyrophosphate-stabilised amorphous calcium carbonates allowed building a cluster-based model paving the way for tunable biomaterials. Abstract : Calcium carbonates and in particular amorphous calcium carbonate (ACC) are of great interest for bone substitution, due to their excellent biocompatibility and ability to release some of the bone mineral constitutive ions. Despite thorough investigations on the ACC precipitation mechanism in the presence of a wide variety of additives to stabilise it, their influence on the composition and structuration of the resulting ACC is rarely finely characterised. In this article, pyrophosphate (Py) was studied as an additive, due to its calcite inhibitor role and the good bioactive properties it demonstrated in vitro and in vivo . A series of pyrophosphate-stabilised ACC (PyACC) powders were synthesised by co-precipitation in water with various amounts of Py, and the structure, composition and multiscale organisation of the resulting compounds were thoroughly characterised. XRD, FTIR spectroscopy and FEG-SEM showed a reduction of the amount and size of calcite crystallites when increasing the Py content, crystallites co-existing with an increasing quantity of the amorphous phase, up to obtaining fully amorphous materials above a certain Py amount. Beyond the stabilising role of Py, and considering SAXS, PDF and solid-state NMR analyses, we proposed an experimental model for PyACC based on a vaterite-like (or proto-vaterite) cluster of 1 nm surrounded by a 2 nm-outer shell containing pyrophosphate ions and pseudo-structural water stabilising the cluster. This comprehensive study and the resulting model are predominant prerequisites to understand the underlying mechanisms of PyACC evolution and could contribute to the rational design of tunable amorphous and bioinspired inorganic bone substitute materials.